SIDOARJO MUD DRAINAGE SYSTEM: SIDOARJO MUD - Achmad Baydhowi; Soebagio (Journal of Civil Engineering Science and Technology (CI-TECH), 2020)
Sidoarjo or Lusi mud has an area of ​​640 ha and an average embankment height of 10 meters and submerges three sub-districts, namely Porong District, Jabon District and Tanggulangin District. In 2018, the Sidoarjo mud embankment has decreased or subsided by up to 8.5 meters at several points, which was caused by the condition of the embankment which was almost full and caused the soil condition of the embankment to become unstable. For this problem, it is necessary to build a drainage channel at the edge of the embankment to overcome the overflow of the embankment and flow it to the Porong river which is on the south side of the Sidoarjo mud embankment. From the calculation of the planned rain discharge, it is found that R2 = 72.95 mm after the planned rainfall is obtained, then the next is to look for the flood discharge plan which then plans the dimensions of the channel on the west and east sides of the embankment after obtaining the dimensions of the channel, then the next is planning the resistance pond and draining it to the porong river. with Siphon Network Pipe